EUROPEAN EXPERIENCE OF STATE ADMINISTRATION OF POLICE AND POSSIBILITY OF HIS USE ORGANS IS IN UKRAINE - Kryshtanovich M.F. (Pressing Problems of Public Administration, 2015)
The main directions of public administration of police activity in EU were analyzed. Themeaning of European experience for Ukraine in police affairs organization was discovered.